2006
DOI: 10.3354/meps323149
|View full text |Cite
|
Sign up to set email alerts
|

Depth-specific differences in growth of the reef sponge Callyspongia vaginalis: role of bottom-up effects

Abstract: Callyspongia vaginalis, a common reef sponge in the Florida Keys, USA, exhibits depthspecific differences in bioenergetics and growth that are a function of food availability. We measured several physiological parameters in situ to construct the bioenergetic budgets of sponges living in deep and shallow waters. Respiration rates were measured in a recirculating flow respirometer and pumping rates were measured by filming dye ejected from sponge oscula. In addition, inhalent and exhalent water sampled from arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
106
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(124 citation statements)
references
References 48 publications
18
106
0
Order By: Relevance
“…Barthel (1986) did not find any correlations between temperature and food availability in the Baltic Sea, and suggested that temperature may be linked with respiration rates to explain growth patterns. Depth-associated picoplankton availability has been implicated in the growth in some Caribbean sponge species (Lesser 2006, Trussell et al 2006 but not others . Duckworth et al (2004) found that sponges grew fastest in areas of high flow and postulated that this may be due to improved delivery of food, which enables sponges to feed with minimal pumping.…”
Section: Growth Rates and Seasonalitymentioning
confidence: 99%
“…Barthel (1986) did not find any correlations between temperature and food availability in the Baltic Sea, and suggested that temperature may be linked with respiration rates to explain growth patterns. Depth-associated picoplankton availability has been implicated in the growth in some Caribbean sponge species (Lesser 2006, Trussell et al 2006 but not others . Duckworth et al (2004) found that sponges grew fastest in areas of high flow and postulated that this may be due to improved delivery of food, which enables sponges to feed with minimal pumping.…”
Section: Growth Rates and Seasonalitymentioning
confidence: 99%
“…While arguable, these criticisms overlook the clear signal in the data from the remaining replicates that supported the first iteration of the experiment: (1) the absence of enhanced sponge growth at the deeper site, indicating a lack of food limitation, and (2) a strong effect of predation at the deeper site where cages were left intact. We maintain that the first iteration of the experiment reported in Pawlik et al (2013) is an unequivocal test of the bottom-up control hypothesis of Lesser (2006), and that the second iteration, while incomplete, supports the first and reveals that the lack of cage controls was a design flaw in Trussell et al (2006).…”
Section: Manipulative Experimentsmentioning
confidence: 99%
“…They seem to want to move this critical depth to 30 m or below, thereby shifting the argument to mesophotic depths. As we explained in our review, the 15 m critical depth was employed to separate sponge populations generally exposed to less and more POC on the basis of a large body of work at Conch Reef, including the manipulative experiments of Trussell et al (2006), who compared depths of 12 and 25 m. Even at mesophotic depths, a gradient of increasing sponge biomass with greater depth is not supported. Using video transects from submersibles, Maldonado & Young (1996) described a dramatic de crease in sponge abundance and species diversity on the Bahamian slope between 100 and 230 m, and a similar decrease in sponge abundance with depth was reported from dredge and trawl studies of the Barbados slope (Lewis 1965).…”
Section: Sponge Distributions and Abundancesmentioning
confidence: 99%
See 2 more Smart Citations